Is brand activism an emotional affair? The role of moral emotions in consumer responses to brand activism - Stefanie Wannow; Martin Haupt; Martin Ohlwein (Journal of Brand Management, 2023)
As brand activism continues to move up the corporate agenda, a more comprehensive understanding of its effects is needed. This paper contributes to the evolving research by investigating moral emotions (i.e. other-praising and other-condemning emotions) as mediating factors and consumer-brand identification (CBI) as a moderator that shape consumer reactions to brand activism. Three scenario-based experiments on two divisive topics show that activist messages elicit moral emotions that determine how individuals respond to them, depending on whether or not they agree with the brand's stance. Moreover, this effect of (dis)agreeing with the brand's stance on brand attitude is moderated by CBI. In case of a strong identification, an activist message does not affect brand attitude as CBI attenuates the activation of moral emotions – both in the positive case of agreement and in the negative case of disagreement. Finally, brand activism may counter the brand's social goals, as it disproportionally motivates opponents of the brand's stand to advocate their own contrary views on the contentious issue. In sum, these findings underscore both the emotional nature of consumer reactions to brand activism and the high level of social responsibility of companies that position themselves as political actors.
Keywords: 330; Brand activism; Brand attitude; Consumer-brand identification; Issue advocacy; Moral emotions